Characterization of Aluminium A356 Composites Reinforced with Silicon Carbide and Titanium Carbide Particulates - Chitrambalam, Thiru (15th International Conference on Advances in Computing, Control, and Telecommunication Technologies, ACT 2024, 2024)
Aluminium A356 is lightweight and highly corrosion-resistant,similar to stainless steel. It finds applications in various fields, from automobile engine blocks to aerospace components. Despite being easily fabricated, it lacks hardness, which impacts its wear resistance. This study focuses on fabricating and testing hybrid composites of Aluminium A356 reinforced with fine silicon carbide and coarse titanium carbide particulates. To maintain the ductility of the matrix, the reinforcement level was limited to 6%. The fabrication process involved the stir casting method. The study evaluated the hardness and wear characteristics of fabricated specimens with varying reinforcement content. © Grenze Scientific Society, 2024.
uGDX
Keywords: Aluminum castings; Aluminum corrosion; Brinell Hardness; Corrosion resistance; Rockwell hardness; Steel corrosion; Titanium castings